2009
DOI: 10.1063/1.3077211
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of temperature profile during magnetic thermotherapy for cancer treatment

Abstract: Magnetic nanoparticles (MNPs) used as heat sources for cancer thermotherapy have received much recent attention. While the mechanism for power dissipation in MNPs in a rf field is well understood, a challenge in moving to clinical trials is an inadequate understanding of the power dissipation in MNP-impregnated systems and the discrepancy between the predicted and observed heating rates in the same. Here we use the Rosensweig [J. Magn. Magn. Mater. 252, 370 (2002)] model for heat generation in a single MNP, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…The authors further compared the derived solution with the experimental data and found an agreement between them. This analytical solution was further verified by Sawyer et al who carried out a study on the heat distribution and found an agreement between their experimental data and Andrӓ et al’s solution [135]. However, it is important to note that the solutions of heat transfer equations derived did not consider the effect of heat loss caused by the blood flow which might affect the heat transfer process significantly in highly perfused tissues.…”
Section: Analytical Modelingsupporting
confidence: 57%
See 1 more Smart Citation
“…The authors further compared the derived solution with the experimental data and found an agreement between them. This analytical solution was further verified by Sawyer et al who carried out a study on the heat distribution and found an agreement between their experimental data and Andrӓ et al’s solution [135]. However, it is important to note that the solutions of heat transfer equations derived did not consider the effect of heat loss caused by the blood flow which might affect the heat transfer process significantly in highly perfused tissues.…”
Section: Analytical Modelingsupporting
confidence: 57%
“…Sawyer et al [135] applied FEM to model the heat transfer process in hyperthermia by using difference approximation method of the differential heat equation. The model described the heat distribution using iron-cobalt as magnetic nanoparticles in MFH for the fat and muscle tissues.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…AMF amplitude is constant) will generate more total heat in tumour regions retaining higher MIONP concentrations, and the local temperature will increase rapidly within zones containing MIONPs when heating commences. Extending beyond the MIONP-containing zones, temperature rapidly declines leading to sharp thermal gradients [6164]. The size or volume of these heat generating zones dominate thermal gradients in their vicinity during the initial stages of heating.…”
Section: Discussionmentioning
confidence: 99%
“…The properties include the magnetic field strength and frequency [36,52,53], eddy current generation [54], nanoparticle mass and size [36,52,55], concentration [52], nanoparticle agglomerates [56] and nanoparticle spatial distributions [38,57,58]. …”
Section: Computational Modeling Of Nanoparticle-based Hyperthermiamentioning
confidence: 99%